2022
DOI: 10.1002/slct.202203386
|View full text |Cite
|
Sign up to set email alerts
|

Schiff Bases Derived from 2‐Amino‐6‐methylbenzothiazole, 2‐Amino‐5‐chloropyridine and 4‐Chlorobenzaldehyde: Structure, Computational Studies and Evaluation of Biological Activity

Abstract: Molecular structure of (E)‐N‐(4‐chlorobenzylidene)‐6‐methylbenzo[d]thiazol‐2‐amine, (E)‐N‐(4‐chlorobenzylidene)‐5‐chloropyridin‐2‐amine was determined in solution and solid states by various techniques such as UV/Vis, FT‐IR, NMR spectroscopy, HRMS and X‐ray diffraction. Both the Schiff base compounds crystallize as monoclinic system with identical space group P21/c. Supramolecular interactions observed in X‐ray structure are validated via density functional theory (DFT) calculations. Further, the reactivities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…These values reflect the semiconductor behavior of these compounds, along with high chemical and kinetic stabilities. The same type of behavior was noticed in compounds recently reported in [57]. Electronic density distributions illustrate that in compounds 1a and 1b, the HOMO densities reside on the chloro-group of the 3-chlorobenzoic acid fragment and its nearest carbon (Figure 10).…”
Section: Frontier Molecular Orbital (Mo) Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…These values reflect the semiconductor behavior of these compounds, along with high chemical and kinetic stabilities. The same type of behavior was noticed in compounds recently reported in [57]. Electronic density distributions illustrate that in compounds 1a and 1b, the HOMO densities reside on the chloro-group of the 3-chlorobenzoic acid fragment and its nearest carbon (Figure 10).…”
Section: Frontier Molecular Orbital (Mo) Analysissupporting
confidence: 80%
“…The 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was used to determine the antioxidant potential (free radical scavenging activity) of the prepared materials and the respective pure starting materials [57]. Samples of about 20 µL and a DPPH reagent volume of 180 µL were loaded into microplate wells.…”
Section: Determination Of Antioxidant Potentialmentioning
confidence: 99%
“…In the case of the Ag(I) polymer, the coordination was evidenced by the shifts of the c, d, and e proton signals compared to the parent spectrum of L1 ( Figure S12 ). In the literature, there are some reports on the decomposition of Schiff bases upon the addition of metal salt [ 34 ], but in the case of our acyclic and macrocyclic Schiff bases, our experimental results indicated that they were highly stable [ 11 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, some of the Schiff bases were also explored and have been reported to carry the notable therapeutic profile [9] . Research disciplines are extensively flooded with a myriad of medicinal properties for instance, anti‐cancer [10] anti‐microbial [11] analgesic [12] etc. The synthetic scheme to attain Schiff base includes condensation of aromatic aldehydes or ketones with primary amines in presence of alcohol by the aid of reflux assembly [13] …”
Section: Introductionmentioning
confidence: 99%